Transmedia Storytelling: from Convergence to Transliteracy - Freire, Maximina Maria (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
Stories and narrative represent meaningful communicative events, typical of human beings’ nature since everybody loves reading, telling, and listening to them. They may also constitute digital events, conveyed through virtual resources, and inserted in the convergence culture (Jenkins, 2006). Within this culture and responding to media expansion, there is transmedia, disseminating diverse but related contents, spread out through multiple media platforms, allowing meaning to converge from one to another. This context supports the transmedia storytelling concept: A transversal narrative process investigated by many researchers, but particularly by Jenkins (2006, 2011), Scolari (2013), and Gosciola (2014). This concept motivates the debate about transliteracy: a synchronized movement across, through and beyond contents and multiple media platforms. Considering this scenario, this article aims at presenting transmedia storytelling conceptually to exploit its potential to promote transliteracy. To reach this goal, transmedia storytelling concepts and features are discussed. After that, considerations are directed towards the transliteracy concept and implications. To conclude, remarks on the target relationship pointed out as the objective of the paper are addressed together with refl ections upon the perception of transmedia storytelling and transliteracy as a concept and an area that are transdisciplinary, respectively